2020
DOI: 10.1111/1759-7714.13447
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the efficacy of immunotherapy and characteristics of specific tumor mutation genes in non‐small cell lung cancer patients

Abstract: Background: Immune checkpoint inhibitors (ICIs) have greatly improved the prognosis and overall management of non-small cell lung cancer (NSCLC) patients, but in the long term less than 20% of patients benefit from treatment with ICIs. Therefore, it is necessary to guide the choice of immunotherapy population through biomarkers in order to maximize the benefit for NSCLC patients. This article mainly explores the relationship between the efficacy of immunotherapy and specific tumor mutation gene characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…We also know now that even targeted cancer therapies impact tumor growth by affecting not just the tumor cells but also the immune system (Deng et al, 2018;Goel et al, 2017). The same is true for the cancer therapies aimed at the immune system that work very differently depending on the genotype of the tumor (Song et al, 2020).…”
Section: Reconciling Synthetic Biology With Ecology and Evolutionmentioning
confidence: 99%
“…We also know now that even targeted cancer therapies impact tumor growth by affecting not just the tumor cells but also the immune system (Deng et al, 2018;Goel et al, 2017). The same is true for the cancer therapies aimed at the immune system that work very differently depending on the genotype of the tumor (Song et al, 2020).…”
Section: Reconciling Synthetic Biology With Ecology and Evolutionmentioning
confidence: 99%
“…In urothelial cancer, PD-(L)1 inhibitors are currently mostly used as second-line treatment for patients with metastatic disease who progressed on platinum-based chemotherapy [ 85 ]. Recent trials investigating the efficacy of checkpoint inhibition in the first-line setting showed no survival benefit for checkpoint inhibitors over chemotherapy in the overall population [ 86 , 87 ].…”
Section: Checkpoint Inhibitor Therapy In Brca-inactivated Tumorsmentioning
confidence: 99%
“…Lung Cancer is one of the most common neoplastic disease and a leading cause of cancer mortality worldwide, approximately 18.4% of all deaths [56][57][58][59]. It has been increasing in certain population such as nonsmokers and female in developing country, while declining in males in most developed countries [56,57].…”
Section: Lung Cancersmentioning
confidence: 99%
“…It has been increasing in certain population such as nonsmokers and female in developing country, while declining in males in most developed countries [56,57]. The most common subtype is non-small cell lung cancer (NSCLC), accounting about 85% [58][59][60]. The majority NSCLC patient are diagnosed at advanced stage, about 50% of them displaying clinically at stage IV and poor prognosis of a five-year survival rate between less than 20% [56][57][58][59][60].…”
Section: Lung Cancersmentioning
confidence: 99%